Social and economic impact of padel in Portugal - the rise of cidade do padel - Abel, Bernardo João Alves (2024)
This thesis investigates the social and economic impact of padel in Portugal, focusing on its rapid expansion and its implications on participation rates, consumer spending, employment, infrastructure development, and media influence. Through a mixed-methods approach combining qualitative and quantitative research, this study reveals that padel has become a key driver of community engagement and local economic growth. The sport has fostered inclusivity, social cohesion, and well-being. It has also generated substantial financial benefits, with significant investments from the private and public sectors. Cidade do Padel’s rise is a pivotal project to professionalize the sport and strengthen Portugal’s positioning in the global padel ecosystem. The study concludes with strategic recommendations for the Portuguese Padel Federation to sustain growth, enhance accessibility, and capitalize on international opportunities.